2020
DOI: 10.1016/s0140-6736(19)32506-1
|View full text |Cite|
|
Sign up to set email alerts
|

Double-duty actions: seizing programme and policy opportunities to address malnutrition in all its forms

Abstract: Key messages  Actions to address undernutrition and overweight/obesity have historically been developed and delivered separately from one another. There is some evidence that programmes addressing undernutrition have unintentionally increased risks for obesity/DR-NCDs in low-and middle-income countries where food environments are changing rapidly. Yet policies and interventions to address undernutrition typically fail to consider these risks. Acronyms BCC Behaviour change communication BMI Body mass index CCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
285
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(303 citation statements)
references
References 97 publications
13
285
0
5
Order By: Relevance
“…Multiple forms of malnutrition are the new normal, according to the GNR 15 and Scaling Up Nutrition 34,35 . Double-duty actions that could simultaneously combat undernutrition, overweight, obesity, and diet-related NCDs have been proposed to address this problem [36][37][38] . Despite progress in identifying such actions, such as the promotion of breastfeeding, double-duty approaches have not been widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple forms of malnutrition are the new normal, according to the GNR 15 and Scaling Up Nutrition 34,35 . Double-duty actions that could simultaneously combat undernutrition, overweight, obesity, and diet-related NCDs have been proposed to address this problem [36][37][38] . Despite progress in identifying such actions, such as the promotion of breastfeeding, double-duty approaches have not been widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Another Ethiopian study also showed that improved dietary diversity is positively associated with household wealth [48] as food choices/diet are driven by price [58]. The increase in being overweight/obesity, despite having a better diet diversity, has been described by Hawkes [9] as the "double-edged sword of malnutrition" because being in a higher wealth strata is likely to increase the risk of being overweight/obesity even though the risk of stunting is reduced. A likely explanation could be that the well-off group can afford to purchase and consume high energy-dense foods and snacks that are made available by the changing and expanding market [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic factors, mainly education and income, have been identified as common drivers of the different forms of malnutrition. Understanding the common drivers presents an opportunity for coming up with interventions that can simultaneously address all forms of malnutrition [9]. In low-income countries, children in the poorest households have been more affected by under-nutrition as they are exposed to suboptimal living conditions like poor sanitation while their better-off counterparts may have better living conditions but suffer from being overweight/obesity [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in some contexts, higher maternal education has also been associated with higher consumption of sugary drinks and more processed foods [ 31 ]. Moreover, although households in the highest wealth groups had a more diverse diet [ 26 , 32 ], they have also been associated with an increase in overweight/obesity [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental cause of the double burden of malnutrition is energy imbalance; “energy excess” for obesity and “energy and nutrient deficiencies” for undernutrition [ 35 ]. Hence the promotion of good nutrition presents an opportunity to avert the occurrence of both forms of malnutrition [ 34 ]. However, there is limited research, in particular concerning the food environments in sub-Saharan African countries, which makes designing holistic and contextualized policies problematic.…”
Section: Introductionmentioning
confidence: 99%